Reconstructing the Essence of Islamic Education from the Perspectives of the Qur'an, Hadith, and Contemporary Islamic Educational Thought - Ahmad Komarudin; Lukmanul Hakim; Yanti Sapitri; M. Iqbal Gelar Budiman; Andewi Suhartini (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze and reconstruct the essence of Islamic education based on the Qur’an, the Hadith, and the thought of classical and contemporary figures. Using a qualitative approach with a literature review method, primary data were obtained from the Qur’an, the Hadith, and authoritative works by Islamic educational figures, while secondary data were obtained from indexed journals and academic books. Data analysis employed content analysis (Krippendorff) and a comparative analysis between Ibn Taymiyyah and Munzir Hitami. The research results indicate that the essence of Islamic education is rooted in divine values aimed at shaping human beings as servants and vicegerents of Allah, through holistic development encompassing spiritual, intellectual, social, and moral dimensions. Surah Al-Bayyinah: 5 and Surah An-Nisa: 1 serve as the main pillars of the theological and epistemological foundations of Islamic education. A comparative analysis of Ibn Taymiyyah (epistemological-theocentric) and Munzir Hitami (teleological-anthropological) reveals common ground in rejecting the dichotomy between religious and secular knowledge, as well as an emphasis on the integration of spiritual, moral, and intellectual values. This integration of values is realized through three pillars: the integration of values (honesty, sincerity, loyalty), the integration of methods (scientific and contemplative), and the integration of goals (worldly and otherworldly happiness). Consequently, a reexamination of the essence of Islamic education is relevant to the development of an integrative education system that combines faith, knowledge, and technology in order to address the challenges of digital disruption and the global moral crisis.